2020
DOI: 10.3390/cancers12071824
|View full text |Cite
|
Sign up to set email alerts
|

DrugSniper, a Tool to Exploit Loss-Of-Function Screens, Identifies CREBBP as a Predictive Biomarker of VOLASERTIB in Small Cell Lung Carcinoma (SCLC)

Abstract: The development of predictive biomarkers of response to targeted therapies is an unmet clinical need for many antitumoral agents. Recent genome-wide loss-of-function screens, such as RNA interference (RNAi) and CRISPR-Cas9 libraries, are an unprecedented resource to identify novel drug targets, reposition drugs and associate predictive biomarkers in the context of precision oncology. In this work, we have developed and validated a large-scale bioinformatics tool named DrugSniper, which exploits loss-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The 5-genomic mutation signature of our risk score model consisted of mutations in CREBBP, KEAP1, RAF1, STK11 and TP53. CREBBP, which encodes an acetyltransferase, has been frequently found to develop mutations in many tumor types (12)(13)(14). At present, there is no literature focusing on the relationship between the CREBBP mutation and immunotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-genomic mutation signature of our risk score model consisted of mutations in CREBBP, KEAP1, RAF1, STK11 and TP53. CREBBP, which encodes an acetyltransferase, has been frequently found to develop mutations in many tumor types (12)(13)(14). At present, there is no literature focusing on the relationship between the CREBBP mutation and immunotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Different chemotherapy schemes applied according to molecular biomarkers could offer new opportunities to patients with LCNEC. The study of Carazo and colleagues [ 14 ] reports an innovative genome-wide loss-of-function screen that may be useful for identifying biomarkers predictive of therapy response, especially for tumors with scarce therapeutic options. Applying this tool, the authors identified CREBBP-defective SCLC to be vulnerable to polo-like kinase 1 (PLK1) inhibition.…”
mentioning
confidence: 99%